THE EFFECT OF EMOTIONAL INTELLIGENCE ON SERVICE QUALITY WITH ORGANIZATIONAL CITIZENSHIP BEHAVIOR AS A MEDIATOR AMONG PADANG RESTAURANT WORKERS IN SOUTH JAKARTA - Aripin, Aripin; Ali, Juhary; Suryanto, Tulus (International Journal of Economy, Education and Entrepreneurship (IJE3), 2024)
The purpose of this study is to look at how emotional intelligence affects the quality of restaurant service, as well as whether OCB plays an intermediary role in the relationship. If OCB proves to be a significant mediator, then emotional intelligence not only directly improves service quality but also encourages positive work behaviors   that contribute to better service. This study uses a quantitative approach. The data was obtained using a questionnaire distributed to 140 employees of Padang restaurants spread across South Jakarta. The results of the study show that emotional intelligence has not been able to improve the quality of service directly. However, emotional intelligence is able to increase OCB which in the end OCB is able to improve the quality of service. The findings of this study have explained that OCB has been proven to play a role as a mediator of emotional intelligence to service quality